Short term performance and microbial community of a sulfide-based denitrification and Anammox coupling system at different N/S ratios. (December 2019) - Qin, Yujie; Wu, Chenglong; Chen, Buqing; Ren, Junyi; Chen, Linyi
Graphical abstract: Highlights: A novel SDAD-Anammox process was developed for nitrogen and sulfide removal. Short term effects of different N/S ratios on SDAD-Anammox activity was obvious. The best TN removal efficiency was 82.8% at a N/S ratio of 2.38. Denitrification contributed to N loss improved with the N/S ratios decreased. Candidatus Kuenenia and Thiobacillius became dominated when nitrate was limited. Abstract: A novel sulfide-based denitrification and Anammox process was established for simultaneous removal of nitrogen and sulfide in a UBF reactor. The effects of the N/S ratio on reactor performance were investigated under five N/S molar ratios (4.56, 2.38, 0.96, 0.73, and 0.51). The best total nitrogen removal efficiency was 82.8% at a N/S ratio of 2.38. When the N/S ratio exceeded 0.96, Anammox contributed to more than 90% of the N loss. Sulfide was completely removed during the full operational period and S 0 accumulation occurred when N/S ratio was less than 1. Thiobacillus (6.1%) and Candidatus Kuenenia (18.8%) were the main functional microorganisms when nitrate was in excess on day 12. As nitrate became limited on day 50, Thiobacillus (21.0%), Sulfurimonas (3.9%), and Candidatus Kuenenia (19.7%) became dominated. In this study, Candidatus Kuenenia was not inhibited by the sulfide.